Peran Dukungan Sosial dalam Meningkatkan Resiliensi pada Remaja Panti Asuhan - nunik hariyani (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2021)
Adolescence can be interpreted as a period of transition of an individual from childhood developing to adulthood. Adolescents are usually associated with periods of change in their life processes. When the individual reaches the age of adolescence, they will begin to think about how their life will be in the future. Adolescents must have great confidence and strong determination so they can quickly get back up from the difficulties in their lives. For every teenager and especially for orphanage youth, of course it is necessary to have the capability to overcome life's difficulties and problems to immediately rise to become a useful and reliable person in carrying out commitments to theirself and the people around them in the future. There are many factors that can influence a person's level of resilience, and one of them is social support. This study aims to see the role of social support in increasing resilience in orphanage youth. This research was conducted using the literature study method. Research with this model is carried out by searching and collecting reference materials from journals and articles based on the variables being studied. After doing this research, it was found that social support had an effect on increasing the resilience of orphanage youth.